Mouse synovial mesenchymal stem cells increase in yield with knee inflammation. Issue 2 (17th November 2014) - Matsukura, Yu; Muneta, Takeshi; Tsuji, Kunikazu; Miyatake, Kazumasa; Yamada, Jun; Abula, Kahaer; Koga, Hideyuki; Tomita, Makoto; Sekiya, Ichiro
ABSTRACT Even though mouse studies have various advantages, harvesting an adequate number of synovial mesenchymal stem cells (MSCs) is difficult in mice. We investigated whether the total yield of MSCs increased in synovium with inflammation in mice. Infrapatellar fat pads (IFPs) were harvested from 10 knees of 5 mice 3, 7, and 14 days after intraarticular injection of carrageenan. Ten IFPs were also harvested from untreated knees as a control. Seven days after initial plating, the total yield of cells was compared among the 4 groups (n = 4–6). The harvested cells were analyzed for multipotentiality and surface epitopes. Furthermore, knee synovitis was compared among the 4 groups in histology. The number of cells in the 3 and 7 days treated group was significantly higher than the other groups. The harvested cells had characteristics of MSCs. Synovitis in the 3 and 7 days treated groups was significantly severer than the other groups. There seemed to be a relationship between the synovitis score and the total yield of cells derived from IFPs. In mice, it became possible to increase the yield 50‐fold by inducing inflammation. This method makes it possible to analyze the molecular mechanisms of cartilage regeneration of synovial MSCs in mice models. © 2014 The Authors. © 2014 The Authors. Journal of Orthopaedic Research published by Wiley Periodicals, Inc. on behalf of the Orthopaedic Research Society. J Orthop Res 33:246–253, 2015.